Introducing the Special Issue on “Ubiquitous Sensing for Smart Health Monitoring” - Bhagat, Yusuf A. (Information (Basel), 2021)
Smart health monitoring for the tracking and diagnosis of physiological issues, early disease detection, prognostication and prevention relies on ubiquitous and unobtrusive monitoring systems, the types of sensors deployed within such systems, sensor networks, data modeling, algorithms and more. The abundance of data generated from smaller, faster, intelligent and more pervasive sensing integrated within our current health monitoring systems has two actionable advantages: (1) to predict health hazards and (2) to improve the underlying sensors in these systems. [...]it is invaluable to explore ever advancing areas such as the design and development of sensors within such systems, novel mechanisms of tracking clinically relevant biometrics, re-purposing known sensing modalities for tracking emerging diseases and reviewing trends in the literature to focus on shortcomings in data acquisition and processing, analysis and study design. Since 2019, over 1300 peer-reviewed articles were published in this very category. [...]the next 20 years may result in a global cost savings of USD 200 billion by increasing healthcare’s reliance on wearable technologies.